Rancang Bangun Aplikasi Perekrutan Pegawai Berbasis Web (Studi Kasus Universitas Universal) - Marfuah, Marfuah; Widiantoro, Suryo (STMIK Palangkaraya, 2018)
Recruitment competition continues to increase because of the high needs for life and the limited needs of work of an organization. There are many enthusiasts who need jobs from various fields of science ranging from work in accordance with their field to cultivate jobs outside their field. The recruitment aspect begins to get special attention, as it can hinder the rate of development of the organization. The organizations needs skilled employer to bring significant leads. Theyhave to develop recruitment strategies and expand the reach of advertising. E-recruitment has several stages that are determined by the organization, using internet media such as WEB to get a decent workforce effectively and efficiently. The application design or conceptual system starting from problem identification, system requirement analysis to design, depiction using a model of Unified Modeling Language as a communication bridge tosome aspects of system, simplify the system development as needed. The design of the application contains the actual process in the recruitment process.